Gender and ICT Usage: Self-Assessment of Critical Issues Facing Indonesia-Thai Gen Y Students' Future by 2030 - Leslie Retno Angeningsih; Bangon Sirisunyaluck (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2018)
Gen Y students, known as Millenials, were born between 1980 and 2000. They account for a third of global population and mostly live in developing countries. This study aims to investigate ICT usage among Indonesian and Thai male and female Gen Y students in self-assessment of critical issues facing their future by 2030. A survey using questionnaires was conducted at the Institute of Community Development (APMD), Yogyakarta, Indonesia and Maejo University, Chang Mai, Thailand. Respondents were selected using random sampling. A total of 316 respondents as the sample of this study were made up of 128 Indonesian and 188 Thai students with response rate of 73.14% and 78.33%, respectively. The results showed that there were significant differences in ICT usage among Indonesian and Thai Gen Y students in their self-assessment toward critical issues they would face by 2030.